Prevalence of smoking and other smoking-related behaviors reported by the Global Youth Tobacco Survey (GYTS) in Thailand - Nithat Sirichotiratana (2012)
Introduction: Thailand ratified the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) on November 8, 2004.The WHO FCTC requires all parties to inform all persons of the health consequences of tobacco consumption and exposure to tobacco smoke. Each party has agreed to develop, implement and evaluate effective tobacco control programs to measure progress in reaching the goals of the WHO FCTC. Methods: The Global Youth Tobacco Survey (GYTS) was developed to provide data on youth tobacco use to countries for their development of youth-based tobacco control programs. Data in this report can be used as baseline measures for future evaluation of the tobacco control programs implemented by the Ministry of Public Health. Results: Overall, about 1 in 10 Thai students are current smokers, this number including 4 times more boys than girls (17% versus 3.9%). Almost 2 in 10 Thai students start smoking before the age of 10, and almost 7 in 10 students are reported to have been exposed to smoke from others in public places. About 4 in 10 students are reported to have an object with a cigarette brand logo on it. Conclusion: The key for Thailand is to implement and enforce the provisions on indirect tobacco advertising, smoking in public places, selling tobacco to youths under 18 years of age, and to use the data from the GYTS to monitor progress toward achieving the goals of the WHO FCTC.When these goals are met, tobacco consumption and exposure in Thailand will have declined substantially.